2021
DOI: 10.1101/2021.02.27.433075
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Small-molecule-mediated OGG1 inhibition attenuates pulmonary inflammation and lung fibrosis

Abstract: Interstitial lung diseases such as idiopathic pulmonary fibrosis (IPF) are caused by persistent micro-injuries to alveolar epithelial tissues together with aberrant repair processes. Despite substantial advancement in our understanding of IPF progression, numerous questions remain concerning disease pathology. IPF is currently treated with pirfenidone and nintedanib, compounds which slow the rate of disease progression but fail to treat underlying causes of disease. The DNA repair enzyme 8-oxoguanine DNA glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In addition to acute pneumonia induced by LPS or TNF‐α, emerging data suggest that OGG1 inhibition by TH5487 attenuates lung fibrosis in a bleomycin model of pulmonary fibrosis 43 . This could indicate that also chronic inflammation can be mitigated by OGG1 inhibition.…”
Section: Suppressing Inflammation Without Suppressing Lymphocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to acute pneumonia induced by LPS or TNF‐α, emerging data suggest that OGG1 inhibition by TH5487 attenuates lung fibrosis in a bleomycin model of pulmonary fibrosis 43 . This could indicate that also chronic inflammation can be mitigated by OGG1 inhibition.…”
Section: Suppressing Inflammation Without Suppressing Lymphocytesmentioning
confidence: 99%
“…In addition to acute pneumonia induced by LPS or TNF-α, emerging data suggest that OGG1 inhibition by TH5487 attenuates lung fibrosis in a bleomycin model of pulmonary fibrosis. 43 This could indicate that also chronic inflammation can be mitigated by OGG1 inhibition. One challenge with immunosuppression in the context of both acute and chronic inflammation is that the immunosuppression itself can have adverse effects.…”
Section: Suppressing Inflammation Without Suppressing Lymphocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…The first evidence implicating OGG1 in fibrotic gene activation came from whole transcriptome analysis, where we found that OGG1-BER-driven signaling triggers airway remodeling programs ( 25 , 26 ). Administration of the OGG1 inhibitor, TH5487, which displaces 8-oxoG from the active binding site of OGG1, decreased tissue remodeling and bleomycin-induced pulmonary fibrosis in murine models ( 27 , 28 ). However, the mechanism of transcriptional reprogramming orchestrated by 8-oxoG-OGG1 complex in fibrotic gene activation remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] We and others have developed potent OGG1 inhibitors which delay lung inflammation in rodent models of disease. [6][7][8] In addition, extensive data has been published on the cellular effects of OGG1 inhibitors in preclinical cancer models. [9][10][11][12] Consequently, the tool compound TH5487 has been applied in a number of studies.…”
Section: Introductionmentioning
confidence: 99%